Theatre Reviews - Rasmus, Agnieszka; Georgopoulou, Xenia (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
Please Continue (Hamlet). Dir. Yan Duyvendak and Roger Bernat. New Classics of Europe Festival. Stefan Jaracz Theatre, Łódź, Poland. Macbeth. The Bible of Darkness. Dir. Theodoros Espiritou. Black Box, Michael Cacoyannis Foundation, Athens, Greece